The management and outcomes of Staphylococcus aureus Bacteraemia at a South African referral hospital: A prospective observational study - Steinhaus, Nicola (Department of Public Health and Family Medicine, 2019)
Staphylococcus aureus is a major human pathogen found worldwide, causing a wide variety of clinical infections. This ranges from skin and soft tissue infections to lifethreatening invasive disease, such as S. aureus bacteraemia (SAB). Despite being a common cause of both community-acquired and hospital-acquired infections, limited evidence exists on the management and outcomes of Staphylococcus aureus bacteraemia (SAB) in resource-limited settings. The aim of this study was to describe a cohort of South African patients with SAB, and explore the factors associated with complicated infection and death. A prospective observational study was performed of patients over the age of 13 years admitted to a South African referral hospital with SAB. Data were analysed using Kaplan Meier survival models and linear regression models. One hundred consecutive SAB infection episodes in 98 patients were included. SAB was healthcare-associated in 68.4%, with 57.6% of these linked to drip site infection; 24.0% of all cases were caused by methicillin-resistant S. aureus (MRSA). Ninety-day mortality was 47.0%, with 83.3% of deaths attributable to SAB. Predictors of 90-day mortality were MRSA (odds ratio (OR) 1.28; 95% confidence interval (CI) 1.0 to 15.1) and the presence of co-morbidities (OR 4.1; 95% CI 1.0 to 21.6). The risk of complicated infection was higher with suboptimal antibiotic therapy (OR 8.5; 95% CI 1.8 to 52.4), female sex (OR 3.8; 95% CI 1.1 to 16.3) and community-acquired infection (OR 7.4; 95% CI 2.0 to 33.1). Definitive antibiotic therapy was suboptimal in 22.6% of all cases. Overall, SAB-related mortality was high. A large proportion of SAB episodes may be preventable, and there is a need for improved antibiotic management in this setting. Part A. The study protocol, as submitted for departmental and ethical approval, is presented here. It includes the background, rationale and methodology of the research done for this mini-dissertation. Part B. A structured literature review is presented of articles pertaining to SAB epidemiology and treatment, with the aim to place this research study in context and identify gaps in research. Part C. A journal-ready manuscript according to the requirements of the International Journal of Infectious Diseases. Appendix. All additional documentation necessary as addendums in the presentation of this mini-dissertation.